Transient Left Ventricular Systolic Dysfunction Associated with Carbon Monoxide Toxicity - Jang, Won Il (Korean Society of Echocardiography, 2010)
Carbon monoxide (CO) is one of well known chemical asphyxiants which cause tissue hypoxia with prominent neurologic and cardiovascular injury. Cardiac dysfunction after CO poisoning can be presented as two clinical patterns. One is transient global left ventricular (LV) dysfunction and the other is LV dysfunction with regional wall motion abnormalities. In this case report, we present a case with transient LV systolic dysfunction caused by intentional exposure to CO. After conservative treatment including high concentration of oxygen, the patient recovered completely without any complication.